Microproteins in skeletal muscle: hidden keys in muscle physiology. Issue 1 (30th November 2021) - Bonilauri, Bernardo; Dallagiovanna, Bruno
Abstract: Recent advances in the transcriptomics, translatomics, and proteomics have led us to the exciting new world of functional endogenous microproteins. These microproteins have a small size and are derived from small open reading frames (smORFs) of RNAs previously annotated as non‐coding (e.g. lncRNAs and circRNAs) as well as from untranslated regions and canonical mRNAs. The presence of these microproteins reveals a much larger translatable portion of the genome, shifting previously defined dogmas and paradigms. These findings affect our view of organisms as a whole, including skeletal muscle tissue. Emerging evidence demonstrates that several smORF‐derived microproteins play crucial roles during muscle development (myogenesis), maintenance, and regeneration, as well as lipid and glucose metabolism and skeletal muscle bioenergetics. These microproteins are also involved in processes including physical activity capacity, cellular stress, and muscular‐related diseases (i.e. myopathy, cachexia, atrophy, and muscle wasting). Given the role of these small proteins as important key regulators of several skeletal muscle processes, there are rich prospects for the discovery of new microproteins and possible therapies using synthetic microproteins.